Lynn Visson: The Complete Russian Cookbook - Davidson, Alan E (Petits Propos Culinaires, 2025)
Lynn Visson: The Complete Russian Cookbook: Ardis Publishers, 2901 Heatherway, Ann Arbor MI 48104: preface by Barbara Norman, no illustrations except for the endpapers, 362 pp., hardcover 15.95.